NIMG-41. PH-WEIGHTED MOLECULAR MRI AS AN EARLY BIOMARKER OF METABOLIC RESPONSE TO IDH INHIBITION IN IDH MUTANT GLIOMAS. (12th November 2021) - Ellingson, Benjamin; Jingwen, Yao; Hagiwara, Akifumi; Nathanson, David; Oughourlian, Talia; Wang, Chencai; Raymond, Catalina; Pope, Whitney; Salamon, Noriko; Lai, Albert; Nghiemphu, Phioanh; Everson, Richard; et al.
Abstract: The current study tested the hypotheses that (1) pH-weighted MRI measurements of tumor acidity reflect glycolytic activity in human gliomas, (2) that tumor acidity, and thus glycolytic activity, differs between human IDH mutant (mIDH) and wild type gliomas, and (3) that an increase in tumor acidity, suggestive of increased glycolytic activity, occurs after inhibition of mutant IDH enzyme activity and reduction in 2HG, an oncometabolite. To test these hypotheses, we employed a custom pH-weighted amine chemical exchange saturation transfer echoplanar (CEST-EPI) technique in 152 patients with IDH mutant or wildtype glioma prior to surgery and 11 patients before and after treatment with AG120 or AG881 enrolled at our institution in a phase 1 perioperative study in patients with recurrent, non-enhancing, IDH mutant low-grade gliomas (NCT03343197). Results from image-guided biopsies in more than 100 patients demonstrated a significant correlation between MTRasym at 3ppm, a measure of tumor acidity from pH-weighted amine CEST-EPI, and expression of key glycolytic proteins including GLUT3 (R 2 =0.2188, P=0.0105), HK2 (R 2 =0.1788, P=0.0314), LDHA (R 2 =0.1111, P=0.0071), and MCT1 (R 2 =0.1228, P=0.0039) as well as ex vivo extracellular flux analysis estimates of ATP consumption from glycolysis (R 2 =0.6684, P=0.0021). Data suggests a significantly lower acidity (MTRasym @3ppm) within non-enhancing tumor in IDH mutant gliomas when compared to IDH wild type gliomas (P< 0.0001). Patients in a phase 1 perioperative study showed a shift toward higher tumor acidity (i.e. higher glycolytic activity) following inhibition of IDH based on 2HG suppression in resected tumors, but at levels below that of IDH wild type gliomas. Levels of 2HG within the tumor after IDH inhibition were inversely correlated with post-treatment tumor acidity (R 2 =0.6342, P=0.0180). Overall, results suggest mIDH gliomas have low levels of glycolytic activity, and successful inhibition of the mutant IDH enzyme results in reduction in 2HG and a measurable metabolic shift toward elevated glycolysis as evidenced using pH-weighted molecular MRI.